The apical/basal-polarity determinant Scribble cooperates with the PCP core factor Stbm/Vang and functions as one of its effectors. - Courbard, J.R.; Djiane, A.; Wu, J.; Mlodzik, M. (Developmental Biology, 2009)
Most tissues display several features of cellular polarization. Besides the ubiquitous epithelial polarization in the Apical-Basal (A/B) axis, many epithelia (and associated organs) display a Planar Cell Polarization (PCP). Recently, a crosstalk between the PCP and A/B polarity determinants has been suggested, i.e. the activity or stability of the PCP factor Frizzled is regulated by the A/B determinants aPKC and Bazooka in the Drosophila eye. We have systematically investigated genetic and physical interactions between the Drosophila A/B factors and the core PCP component Strabismus (Stbm)/Van Gogh (Vang). The A/B determinant Scribble was found to interact both genetically and physically with Stbm/Vang. We demonstrate that Scribble binds Stbm/Vang through its PDZ domain 3 and that it cooperates with Stbm/Vang in PCP establishment. Our data indicate that Scribble, in addition to its role in A/B polarity, has a distinct requirement in PCP establishment in the Drosophila eye and wing. We define a scribble allele that is largely PCP specific. Our data show that Scribble is part of the Stbm/Vang PCP complex and further suggest that it might act as an effector of Stbm/Vang during PCP establishment.